Unfavorable variants of folate metabolism genes in patients with acute coronary syndrome in non-obstructive coronary atherosclerosis - V. V. Ryabov; S. B. Gomboeva; Yu. D. Lugacheva; I. B. Kulagina; R. P. Karpov (Российский кардиологический журнал, 2018)
Aim. To study the occurrence of allelic variants of folate cycle enzymes’ genes, which are unfavorable with respect to the risk of thrombophilia, to analyze the serum level of homocysteine, and to assess their impact on the development of acute coronary syndrome (ACS) in non-obstructive coronary atherosclerosis (NOCA). Material and methods. The material for the study was the results of a non- randomized, open, controlled conduct research, NCT02655718' conducted in 2015-2016 in the emergency cardiology department. The sampling included patients older than 18 years with ACS and NOCA, confirmed by invasive coronary angiography (ICAG). Patients who had previously undergone coronary artery revascularization were excluded from the study. We analyzed four polymorphic genotypes of folate cycle enzyme genes of included patients: methylene-tetra- hydro-folate-reductase MTHFR (677 C>T, 1298 A>C), methionine synthetase MTR (2756 A>G), methionine synthetase reductase MTRR (66 A>G). Determination of genotypes was performed using the methods of polymerase chain reaction and the use of a set of reagents produced by OOO “DNK-Tekhnologiya”. The level of homocysteine was determined by the enzyme immunoenzyme technique using Axis (UK) set of instruments for diagnosis and standards methods.Results. In 2015-2016 913 patients with ACS were hospitalized in emergency cardiology department; 44 (4.8%) were patients with NOKA. The mean age was 54±11 years (68% men). Mean level of homocysteine in the examined patients was 12,2 (10,8; 13,6) umol/l, in men — 12,4 umol/l (11,5; 13,6), in women — 11,3 umol/l (9,5; 13,2). Hyperhomocisteinemia (HHC) was registered in 8 (18%) individuals. The median level of homocysteine in patients with HHC was 22,8 (17,2; 25). An increase in the ultra-sensitive C-reactive protein and diagnosing of acute myocardial infarction (AMI) were more common in patients with HHC. The level of homocysteine did not differ in patients with various degrees of coronary artery stenosis; it was associated with age, hereditary background, smoking and the carriage of an unfavorable homozygous polymorphic variant of the TT genotype MTHFR gene (677 C>T). The carriage of the unfavorable TT genotype MTHFR (677 C>T) was statistically significantly more common in patients with AMI. The carriage of unfavorable homo- and heterozygous genotypes of the MTHFR gene (677 C>T) in the group without HHC was also detected. The ancestral allele C of the rs1801133 gene was statistically significantly more common in intact coronary arteries. Conclusion. In this study 96,6% of patients with ACS and NOCA were carriers of unfavorable polymorphic variants of folate metabolism genes. The carriage frequency of unfavorable T allele of rs1801133 gene is statistically significantly more common in patients with AMI. The presence of this genotype is associated with the development of HHC, which is equivalent of literature data. However, the presence of the allelic variant of TT MTHFR (677 C>T) did not always lead to the development of HHC. An increase in plasma homocysteine levels is directly proportional to age, hereditary background, smoking, and carriage of the TT rs1801133 genotype. It is also associated with an increased risk of AMI, which confirms previous studies.